Brown seaweed hydrolysate as a promising growth substrate for biomass and lipid synthesis of the yeast yarrowia lipolytica - Dobrowolski, Adam; Nawijn, Willem; Mirończuk, Aleksandra M. (Frontiers in Bioengineering and Biotechnology, 2022)
Biomass of the brown algae Fucus vesiculosus and Saccharina latissima is a promising, renewable feedstock because of the high growth rate, accessibility and content of glucose and mannitol. Saccharification of seaweeds is a simple process due to the lack of lignocellulose in the cell wall. The high content of glucose and mannitol makes these seaweeds an attractive feedstock for lipid production in the yeast Yarrowia lipolytica. This study demonstrated that hydrolysates of brown algae biomass can be applied as a substrate for synthesis of yeast biomass and lipids without any supplementation. To increase the lipid titer in yeast biomass, we employed an engineered strain of Y. lipolytica overexpressing DGA1/DGA2. In consequence, the C/N ratio has a lower impact on lipid synthesis. Moreover, the applied substrates allowed for high synthesis of unsaturated fatty acids (UFA); the level exceeded 90% in the fatty acid pool. Oleic (C18:1) and linoleic acids (C18:2) achieved the highest content. The study showed that Y. lipolytica is able to grow on the seaweed hydrolysate and produces a high content of UFA in the biomass.